The Industrial Committee of the Medical Society of Kraków (1886–1912) - Monika Zamachowska (Folia Historica Cracoviensia)
The Industrial Committee of the Medical Society of Kraków (1886–1907) was established to protect and support the Polish medical industry. In the absence of the official Polish state existed, the activities of the committee provided support for Polish manufacturers and health resorts. The main activity of the committee members consisted in assessing production technology and analysis of the chemical composition of food products, and additional clinical trials of medications. In the case of health resorts, evaluation extended to their infrastructure, technical solutions for spa treatments, and curative properties of the waters and climate. Positively evaluated products and spas received a particular certificate and were officially recommended by the society. As many members of the committee were scientists of world renown who belonged to the social elite, using the products they recommended became fashionable and offered a realistic advantage against foreign competition.